Evaluating Sixth-Grade Biology Textbook Through William Rumi Method: Insights for Digital and Interactive Learning Media - Sharafie, Darioush (Assyfa Learning Journal, 2025)
This research employs the William Rumi content analysis method to examine the biology section of Iran’s sixth-grade elementary science textbook, focusing on lessons 10–13. It assesses the text, questions, and images, categorizing them as active, passive, or neutral. The study finds the main text is largely passive, with an engagement coefficient of 0.32, while the questions encourage active learning with a coefficient of 1.50. Images offer minimal engagement, with a coefficient of 0.42. These results underscore the necessity to bolster active learning elements and enhance the use of images. The analysis provides guidance for developing interactive digital textbooks and adaptive, technology-enhanced learning resources, consistent with global educational technology trends. By embedding active learning strategies and digital interactivity, student engagement can be heightened, catering to diverse learning needs in both formal and non-formal educational contexts.